School culture patterns for curriculum reform adaptation across two junior high schools - Arina, Arina; Rahmawati, Tina (ARKA INSTITUTE, 2025)
This multi-case qualitative study compares how organizational culture supports adaptation to Kurikulum Merdeka in two junior high schools in Gunung Mas Regency, Central Kalimantan, Indonesia: SMPN 6 Kurun in Kuala Kurun and SMPN Satu Atap 1 Kurun in Desa Penda Pilang. Seven internal actors participated. Data were generated through semi-structured interviews, observations, and document review, and analyzed using first-cycle coding and axial coding, supported by within-case memos and cross-case synthesis. The findings show two contrasting organizing logics. Implementation in SMPN Satu Atap 1 Kurun was shaped by feasibility-driven adjustments that protected instructional continuity under access and capacity constraints. Routines for attendance, scheduling, and documentation remained flexible so that evidence work did not displace teaching time. In SMPN 6 Kurun implementation relied on consolidation through scheduled supervision, role distribution, and routine monitoring that stabilized coordination and enabled more consistent follow-up using documents. The study contributes a mechanism-oriented explanation of reform adaptation by showing how sensemaking, coordination routines, and accountability artefacts translate policy expectations into daily practice.